ANALYSIS OF SPEECH ACTS USED BY DIGITAL CONTENT CREATORS IN ENDORSEMENT VIDEOS OF BEAUTY PRODUCTS - Hajar Hajar; Sartika Sailuddin; Sutisno Adam (Tekstual, 2024)
This study aims to analyze the form of speech acts used by content creators in beauty product endorsement videos on TikTok platform. The research method used is qualitative collecting the data of utterances found in beauty products endorsement videos posted by TikTok content creators. Nine videos were selected from three top beauty content creators who have the highest number of followers. Three videos picked from each beauty content creator were based on the engagement rate that the video got (i.e. number of comments, number of views, and number of likes). The utterances were analysed by applying J.L. Austin's (1962) speech act theory to categorize the types of speech acts at the three levels of locution, illocution, and perlocution, which are used in digital promotional videos. The results showed that content creators mostly used directive and assertive speech acts in their endorsement videos. At the perlocutionary level, comment sections were observed and it was found that the selection of speech acts have created a sense of resonance to the audiences; thus, influencing their evaluations to the promoted products. These findings have brought implications on how communicative actions can shape brand identity leading to audiences engagement and trust towards the products.